5-HT7 Receptor Is Involved in Electroacupuncture Inhibition of Chronic Pain in the Spinal Cord - Yuan, Xiao-Cui; Yan, Xiang-Ji; Tian, Li-Xia; Guo, Yi-Xiao; Zhao, Yu-Long; Baba, Sani Sa’idu; Wang, Yu-Ying; Liang, Ling-Li; Jia, Hong; Xu, Lin-Ping; Li, Li; Lin, Han; et al. (Frontiers in Neuroscience, 2021)
Knee osteoarthritis (KOA) is a common and disabling condition characterized by attacks of pain around the joints, and it is a typical disease that develops chronic pain. Previous studies have proved that 5-HT1, 5-HT2 and 5-HT3 receptors in the spinal cord are involved in electroacupuncture (EA) analgesia. 5-HT7 receptor plays antinociceptive role in the spinal cord. However, it is unclear whether 5-HT7 receptor is involved in EA analgesia. The 5-HT7 receptor is a stimulatory G-protein (Gs) coupled receptor that activates adenylyl cyclase (AC) to stimulate cyclic adenosine monophosphate (cAMP) formation, which in turn activates protein kinase A (PKA). In the present study, we found that EA significantly increased the tactile threshold and the expression of 5-HT7 receptor in the dorsal spinal cord. Intrathecal injection of 5-HT7 receptor agonist AS-19 mimicked the analgesic effect of EA, while a selective 5-HT7 receptor antagonist reversed this effect. Moreover, intrathecal injection of AC and PKA antagonists prior to EA intervention prevented its anti-allodynic effect. In addition, GABAA receptor antagonist Bicuculline administered (i.t.) prior to EA intervention blocked the EA effect on pain hypersensitivity. Our data suggest that the spinal 5-HT7 receptor activates GABAergic neurons through Gs-cAMP-PKA pathway and participates in EA mediated inhibition of chronic pain in a mouse model of KOA.